Efektivitas Konseling Kelompok dengan Teknik Self-Management untuk Mereduksi Prokrastinasi Akademik Siswa Kelas VIII di SMPN 3 Cilimus Kuningan - Alya Nurkhalizah; Bambang Setiawan; Rina Kurnia (UIN Siber Syekh Nurjati Cirebon, 2025)
Academic procrastination is a behavior of delaying the completion of tasks that can have a negative impact on students' academic achievements. This behavior can be caused by students' mindsets, habits, and personality traits (Ferrari, 1995). One of the approaches to overcome this problem is the self-management technique, which is the individual's ability to manage their thoughts, emotions, and behaviors independently to achieve certain goals. This technique can be applied through group counseling services, which is the process of providing assistance in a small group atmosphere that is open and mutually supportive, with the aim of encouraging behavior change in a more positive direction. This research aims to: (1) identify the profile of academic procrastination of class VIII students at SMPN 3 Cilimus; (2) design group counseling services with self-management techniques that suit the needs of students; and (3) find out the effectiveness of the service in reducing academic procrastination. The research uses a quasi-experimental method with a pretest-posttest control group design. The population in this study is all class VIII students at SMPN 3 Cilimus as many as 101 students. The sample was selected from the class with the highest academic procrastination score. This research refers to Prayitno (1995) which states that the ideal number of group counseling members ranges from 6 to 10 people, in order to maintain the effectiveness of group dynamics and active participant involvement. The results of the Independent Samples T-test showed a significance value (Sig. 2-tailed) of 0.000 (< 0.05), which indicated a significant difference between the experimental and control groups after the intervention. N-gain test results show effectiveness in the medium category. Thus, group counseling services with self-management techniques are quite effective in reducing the academic procrastination of class VIII students at SMPN 3 Cilimus.